Modified Gatot Score has a better Specificity in Predicting Ovarian Malignancies Compared to Risk Malignancy Index - Shirley Mansur (Indonesian Journal of Obstetrics and Gynecology, 2013)
Objective: The study was designed to evaluate the sensitivity and specificity of several methods in detecting ovarian epithelial malignancy by comparing Gatot Score and Risk Malignancy Index, and also proposing the modification of Gatot Score. Methods: Four hundred and one subjects with suspected epithelial ovarian malignancy were subjected to the study and had anamnesis, physical examinations, laboratories studies and ultrasonography performed. From the data, we took the variables according to Gatot Score and Risk Malignancy Index. We performed statistic analysis in term of sensitivity, specificity, ROC and optimal cut-off-point. Result: From 401 observation subjects, revealed that Gatot Score possess the sensitivity of 73.7% and specificity of 45.6% (p = 0.000; LR 28.830), while RMI possess the sensitivity of 72.4% and specificity of 35.94% (p = 0.02, LR 9.588) for RMI 1, and the sensitivity of 76% and specificity of 30.9% (p = 0.05; LR 7.984) for RMI 2. Modification to Gatot Score was performed by re-weighting to its all variables, which resulted in Gatot Score Modification 1 with cut-off point of 28.5, sensitivity of 60.4% and specificity of 35.94% (p= 0.000, LR 44.228) and Gatot Score Modification 2 with cut-off point of 5.75, sensitivity range between 49.3-69.6% and specificity range between 51.6-65.2% (p = 0.000; LR 36.806). Conclusion: Both Gatot Score and RMI gave unsatisfactory output in predicting the malignancy of ovary. By reassigning the weighting of all variables in Gatot Score, the sensitivity and especially the specificity was improved in detecting the malignancy of epithelial type ovary. This measure was directed for patients in reproductive ages, thus increasing the possibility of true malignancy. [Indones J Obstet Gynecol 2013; 37-2: 113-6] Keywords: Ca-125, epithelial ovary tumor, Gatot score, risk malignancy index